Molecular diversity within lineage 7 isolates of Fusarium graminearum schwabe from an international collection - Cumagun, Christian Joseph R.; Parzies, Heiko K.; Miedaner, Thomas (2006)
Thirty-eight isolates of Fusarium graminearum from a worldwide collection were analyzed by amplified fragment length polymorphism (AFLP) to determine the amount of molecular diversity within lineage 7. On the basis of AFLP profiles, a high level of genetic diversity among isolates was found with a mean genetic similarity of 0.21 and genetic diversity of 0.41. This suggests a high adaptability of F. graminearum to different environmental conditions and a large population size of lineage 7. Grouping of isolates with respect to host or geographical origin was not evident.
Keywords: genetic diversity; Plant diseases